Intraoperative transesophageal echocardiographic predictors of recurrent left ventricular outflow tract obstruction in children undergoing subaortic stenosis resection. Issue 5 (13th February 2018) - Nawaytou, Hythem M.; Mercer‐Rosa, Laura; Channing, Alexandra; Cohen, Meryl S.
Abstract : Background: Intraoperative transesophageal echocardiography (iTEE) is used to assess for residual left ventricular outflow tract obstruction (LVOTO) after surgical resection of subaortic membrane causing subaortic stenosis (sub‐AS). We aimed to identify the iTEE features associated with recurrence of LVOTO. Methods: We conducted a retrospective study of children undergoing sub‐AS resection from June 2006 to June 2014. Doppler assessment of the flow velocity and the anatomical features of the left ventricular outflow tract were analyzed from stored echocardiograms. Recurrent LVOTO was defined as an increase in the mean pressure gradient across the left ventricular outflow tract of > 15 mm Hg on the most recent follow‐up echocardiogram from the mean pressure gradient on the predischarge echocardiogram or as doubling of the mean pressure gradient to a value ≥20 mm Hg. Results: Thirty‐five patients were included, with median age at surgery was 8.1 years (range: 0.7–29 years) and median follow‐up was 47 months (2–91 months). Ten patients (29%) had recurrent LVOTO, which was associated with a shorter distance between the narrowest diameter of the outflow tract and the aortic valve on iTEE [median 0.59 cm (range 0.39–0.74) vs 0.98 cm (0.75–1.5), P = .03]. No patients with more than mild residual LVOTO on iTEE regressed to mild or no LVOTO on follow‐up echocardiograms. Conclusions: LVOTO recurrence after sub‐AS resection is common, and residual LVOTO remains the same or increases over time. Proximity of the LVOTO to the aortic valve is a risk factor for recurrent LVOTO. These findings may be useful in counseling patients and to guide the frequency of postoperative follow‐up.